(untitled) - Díaz Osorio, José; Valdés, Rodrigo; Hernández, Nicole (Universidad Nacional de Cuyo. Facultad de Ciencias Agrarias)

Chilean wine in the european market : a positioning mapping approach from Germany (2015)
Current wine marketing requires a rethinking of business strategy in order to increase the current market share and international prestige. This paper provides a comparative diagnosis of the positioning of Chilean wine in the European market, focusing on the case of Germany. The working methodology was based on the registering and market segmentation of the selection of wines on display on the shelves of supermarkets, hypermarkets and specialty stores. Subsequently, a comparative analysis was performed in order to evaluate the growth dynamism of this target market from 2001 to 2013. The results show an increase from one period to another in the prices of national wines, and both an increase in and diversification of the supply in the German market. Chile, with its share in a wide range of prices, has become a more prominent competitor, and has managed to attain higher price ranges as compared to 2001. Currently, when it comes to Carmenere and Merlot, Chile appears as it is the only country offering this varietal in the German market. This is a situation that should be strengthened using commercial strategies that allow for a more aggressive positioning of this varietal. Lastly, it is recommended to adopt a more aggressive positioning method for Chilean wine, using a country-strategy that improves its long-term competitiveness.